Kraft Pulping of Thuja orientalis Linn. - Singh, S. V. (Indian Forester, 1974)
An investigation on the suitability of Thuja orientalis L., for the production of kraft paper showed that the yield of the pulp and the strength properties are comparable with those obtained from other conifers tested in this laboratory.